Analysis of Service Quality Gaps and Strategic Improvement Priorities: A Comparative Study of Customer Satisfaction at Minimarkets using SERVQUAL and Importance Performance Analysis - Anggoro P. Utomo; Roland Y.H. Silitonga; Alexander G. Agung (The Indonesian Institute of Science and Technology Research, 2026)
This study conducts a comparative analysis of service quality between two competing minimarkets in Indonesia: Pindadmart (a state-owned enterprise affiliate) and Alfamart (a market leader). The objective is to identify performance gaps and formulate strategic improvement priorities. The research employs a dual-methodological approach utilizing the SERVQUAL model to measure the gap between customer expectations and perceptions across five service dimensions (Tangibles, Reliability, Responsiveness, Assurance, Empathy), and Importance-Performance Analysis (IPA) to map service attributes and identify areas requiring immediate managerial attention. Data were collected via questionnaires from 110 respondents, evenly distributed between the two retailers. The results reveal a significant service quality deficit at Pindadmart, which exhibits a larger negative gap score (-1.20) compared to Alfamart (-0.77). The most critical gap for Pindadmart lies within the Empathy dimension, specifically concerning employee attentiveness to customer needs (Gap = -1.67). The IPA matrix positions attributes such as adequate parking (P3) and employee trustworthiness (P16) in the high-priority quadrant for Pindadmart. This study conceptually and empirically links perceived empathy failures to underlying operational deficiencies, specifically product stockouts, arguing that customers interpret inventory unavailability as a lack of organizational care. Recommendations focus on synergizing operational improvements in inventory management with enhancements in physical facilities and employee training to bolster customer satisfaction and fulfill the cooperative’s role in mentoring local MSMEs.